The Application of distributed discrete event simulation algorithms to concatenated local-area and Wide-area Network (CLOWN) Simulator - Carreon, Mario (Philippine computing journal)
The concatenated LOcal-area and Wide-area Network or CLOWN simulator is a network simulator programmed using object-oriented C that runs on a single processor...